2014
DOI: 10.1016/j.prosdent.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surface modification on the retention strength of polyetheretherketone crowns adhesively bonded to dentin abutments

Abstract: STATEMENT OF PROBLEM: The mechanical properties of polyetheretherketone (PEEK) make it an ideal material for fixed dental prostheses; however, insufficient information is available about the cementation of these restorations. PURPOSE: The purpose of this study was to evaluate the retention strength of differently pretreated and conditioned PEEK crowns luted to dental abutments. MATERIAL AND METHODS: Human teeth were prepared in a standardized manner, and PEEK crowns were milled (N=160, n=10 per group) and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
135
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 119 publications
(143 citation statements)
references
References 19 publications
4
135
2
2
Order By: Relevance
“…The resulting pontics (Fig. 1b) [14,15,16,20,21,24] with this material, conditioning was carried out by wetting the frameworks with a thin film using a microbrush which was immediately polymerized for 90 s (intensity: 220 mW/cm², Brelux Power Unit; bredent) ( Fig. 1c), before a thin film of opaquer (Opaquer combo.lign; bredent) was applied and polymerized for 360 s (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting pontics (Fig. 1b) [14,15,16,20,21,24] with this material, conditioning was carried out by wetting the frameworks with a thin film using a microbrush which was immediately polymerized for 90 s (intensity: 220 mW/cm², Brelux Power Unit; bredent) ( Fig. 1c), before a thin film of opaquer (Opaquer combo.lign; bredent) was applied and polymerized for 360 s (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of studies of bond strength between veneering resin composite and PEEK-framework have been performed already, in which different pre-treatments of the airborne-particle abraded surface with piranha-etching [13,14,15,16], sulfuric acid [5,9,12,17] and cold plasma treatment [18,19] were tested, providing, however, some conflicting results. Some of these studies examined the influence of the adhesive on the bond strength to PEEK and the vast majority showed nevertheless adequate bonding results with MMA-based adhesive materials comparable to those of conventional framework materials like ceramic or metal alloys [14,15,16,20,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have investigated the bonding characteristics of PEEK and composite resins, 3,4,[6][7][8][9][10][11][12][13][14] and several studies have reported that a surface pretreatment using sulfuric acid improved the bond strength to composite resin materials. 3,4,6,13 Some studies also assessed the bond strength of resin cements after etching with piranha solution.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,6,13 Some studies also assessed the bond strength of resin cements after etching with piranha solution. 8,9,11,15 These studies, however, reported conflicting results: While some studies observed no effect of piranha acid etching on the bond properties, 8,9,15 one investigation reported higher bond strength, especially when applying an adhesive on airborne-particle-abraded and piranha-etched PEEK as compared with etching alone. 11 In addition, the influence of different adhesives on bond strengths to PEEK has also been investigated.…”
Section: Introductionmentioning
confidence: 99%